2008
DOI: 10.1111/j.1751-9004.2008.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Psychology and Media: Critical Considerations

Abstract: In this paper, we argue that media saturate everyday living, and that people engage with and are engaged by media in diverse and complex ways. We suggest a need for an informed social psychology of media that conceptualises media as social practice, and attends to media practices as they occur. We propose that much media psychology research is limited because it: (i) focuses too strongly on documenting causal, and usually negative, media effects; (ii) continues to apply unsuitable research methodologies and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…We have shown that the meaning of places and objects are never definitive. Objects such as an MP3 player do not simply enter everyday life, they are created there; their meaning arises from the social practices through which they are engaged (Chamberlain & Hodgetts, 2008). Brett's MP3 player becomes an habitual aspect of his everyday life, used to construct a sense of place and home on the move.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the meaning of places and objects are never definitive. Objects such as an MP3 player do not simply enter everyday life, they are created there; their meaning arises from the social practices through which they are engaged (Chamberlain & Hodgetts, 2008). Brett's MP3 player becomes an habitual aspect of his everyday life, used to construct a sense of place and home on the move.…”
Section: Discussionmentioning
confidence: 99%
“…We have come to accept through research in human geography and other disciplines that there is a privileged voice that operates over the top of another that is silenced. Mainstream media tend to represent images of marginalised groups (human and nonhuman), which are exaggerated and/or manipulated (Chamberlain & Hodgetts, 2008). Animals, especially pets, provide opportunity for deep experience, companionship, (social) well-being, warmth and humour, which advertisers attempt to tap into when they use animal imagery in persuasive messages (Lancendorfer et al, 2008).…”
Section: Media Geographies: Approaching Animals In Advertisingmentioning
confidence: 99%
“…Yksilön mediasuhde on sosiaalisesti, kulttuurisesti ja paikallisestikin muovautunut (ks. Chamberlain & Hodgetts 2008;Hakkarainen 2009). Vastaavasti tietokonetta käyttävien ikääntyneiden osalta on osoitettu, että sosiaalisen lähiympäristön tuella on keskeinen merkitys mielenkiinnon heräämisessä, käytön oppimisessa sekä käytön ja osaamisen ylläpidossa (ks.…”
Section: Tietokoneen Käytön Vaatima Aika On Passivoivaa Ja Jäykistää unclassified
“…Kuitenkin tulokset viittaavat myös siihen, että kronologisen iän ja koulutustason lisäksi tietokoneettoman elämän valinta selittyy myös sosiaalisilla, kulttuurisilla ja paikallisilla tekijöillä (ks. myös Chamberlain & Hodgetts 2008;Hakkarainen 2009;Sourbati 2009). Vastaajiemme tietokoneettomassa elämässä on kyse myös maalaiskylissä ja taajamien omakotialueilla rakentuvasta elämäntavasta (ks.…”
Section: Olen Ajatellut Että Ehkäpä Sitten Jos Joudun Vanhainkodin Sunclassified